Management of innovation ecosystems based on six sigma business scorecard - Calado, João Manuel Ferreira (2019)
In the present context, companies to be competitive must develop high-performance innovation capabilities that enable them to respond quickly to market needs. However, the lack of tools and methodologies to assess the performance of innovation projects in an integrated way remains an obstacle. The paper begins by discussing the principles of Six Sigma and the Balanced Scorecard for performance evaluation. Next, the advantages of the Six Sigma Business Scorecard are discussed as a tool to support the evaluation of performance in innovation projects. Finally, the advantages of their application in the context of a collaborative ecosystem are discussed. It is illustrated that the BSC ensures that top management pays attention at any time to the specific elements of the Six Sigma implementation that are not working as planned, providing a link between strategy and quality initiatives assuring customers satisfaction in innovation projects.